2001
DOI: 10.1175/1520-0442(2001)014<2105:epdvau>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

ENSO, Pacific Decadal Variability, and U.S. Summertime Precipitation, Drought, and Stream Flow

Abstract: The relationship between the three primary modes of Pacific sea surface temperature (SST) variability-the El Niño-Southern Oscillation (ENSO), the Pacific decadal oscillation, and the North Pacific mode-and U.S. warm season hydroclimate is examined. In addition to precipitation, drought and stream flow data are analyzed to provide a comprehensive picture of the lower-frequency components of hydrologic variability.ENSO and the two decadal modes are extracted from a single unfiltered analysis, allowing a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
326
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(361 citation statements)
references
References 65 publications
30
326
1
4
Order By: Relevance
“…• variability of El Niño-southern oscillation (ENSO) teleconnections (Elliot and Angell, 1988;Zhang et al, 1997;Kruger, 1999;McCabe and Dettinger, 1999;Power et al, 1999a;Mason, 2001); • the Pacific decadal oscillation (PDO; Mantua et al, 1997;Barlow et al, 2001; • variability of North Atlantic oscillation (NAO) teleconnections (Hurrell, 1995);…”
Section: Dmdos In Precipitation and Runoff Have Been Linked Tomentioning
confidence: 99%
See 1 more Smart Citation
“…• variability of El Niño-southern oscillation (ENSO) teleconnections (Elliot and Angell, 1988;Zhang et al, 1997;Kruger, 1999;McCabe and Dettinger, 1999;Power et al, 1999a;Mason, 2001); • the Pacific decadal oscillation (PDO; Mantua et al, 1997;Barlow et al, 2001; • variability of North Atlantic oscillation (NAO) teleconnections (Hurrell, 1995);…”
Section: Dmdos In Precipitation and Runoff Have Been Linked Tomentioning
confidence: 99%
“…• Australia (Warner, 1987;Power et al, 1999b); • North America (Cayan et al, 1998;Hamlet and Lettenmaier, 1999;Barlow et al, 2001;Neal et al, 2002);…”
Section: Introductionmentioning
confidence: 97%
“…The third mode in the NH is a combination of these two modes. Barlow et al (2001) suggested that the NP mode dominated both in the JFM and JAS seasons. Actually, the second mode in the NP in the JAS season has a similar pattern to that in the JFM season.…”
Section: Dominant Variation Modes In the Global Sst Fieldmentioning
confidence: 99%
“…Specifically, the El Niño-Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO) influence precipitation and streamflow patterns in the United States (Barlow et al, 2001;McCabe and Dettinger, 2002;McCabe et al, 2007). ENSO is a coupled oceanatmosphere phenomenon affecting the climate.…”
Section: Introductionmentioning
confidence: 99%
“…The warm phase of the PDO tends to coincide with anomalously cool temperatures and wet periods in the southern United States (Mantua and Hare, 2002). Barlow et al (2001) found that the three primary modes of Pacific variability (e.g., ENSO, PDO and the North Pacific mode) strongly influence US warm season precipitation and stream flow. McCabe and Dettinger (2002) demonstrated that the PDO is responsible for the majority of inter-annual variability in the April 1 snowpack in the western United States.…”
Section: Introductionmentioning
confidence: 99%